2003
DOI: 10.1046/j.1468-2982.2003.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

What Kind of Habituation is Impaired in Migraine Patients?

Abstract: The acoustically evoked cortical potentials of 20 migraine patients were investigated using a combined conditioning-testing and oddball paradigm. The short- and long-term habituation results of the P50 and P300 waves were compared with 16 healthy subjects. Migraineurs were characterized by a sensory gating deficit of the P50 wave (reduced short-term habituation) in the non-target condition and a reduced long-term habituation of the P300 wave in the target condition. The study describes disturbances of informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
3
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 36 publications
6
53
3
3
Order By: Relevance
“…The study of sensory gating of the auditory P50 response [65] showed a marked reduction of gating in patients compared to healthy volunteers, which suggests that lack of habituation in migraine might result in part from a precortical dysfunction. A reduced sensory gating of the P50 wave in migraine patients was confirmed by another study [66] and considered as an expression of reduced short-term habituation.…”
Section: Auditory Cortex Response Patterns In Migrainementioning
confidence: 64%
“…The study of sensory gating of the auditory P50 response [65] showed a marked reduction of gating in patients compared to healthy volunteers, which suggests that lack of habituation in migraine might result in part from a precortical dysfunction. A reduced sensory gating of the P50 wave in migraine patients was confirmed by another study [66] and considered as an expression of reduced short-term habituation.…”
Section: Auditory Cortex Response Patterns In Migrainementioning
confidence: 64%
“…In both of these cases and other habituation paradigms in Drosophila (Corfas and Dudai 1989;Engel and Wu 1996;Jin et al 1998;Engel et al 2000) and other models (Harris 1943;Thomson and Spencer 1966;Hawkins 1988;Rose and Rankin 2001;Deshmukh and Bhalla 2003;Siniatchkin et al 2003), emergence of habituation was observed after a "refractory" period or number of stimuli, during which animals responded as if they were naive. This suggests that within this time frame, processes that normally prevent premature habituation become inactivated, ones that mediate habituation are activated, or both.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, since habituation may underlie selective attention (Groves and Thomson 1970;Freedman et al 1991;Gillberg 2003), its premature onset could impair adequate discrimination between novel and preexperienced stimuli. Habituation deficits have been associated with schizophrenia (Freedman et al 1991;Adler et al 1999;Gillberg 2003;Meincke et al 2004), learning disabilities (Gillberg 2003;Slaats-Willemse et al 2003), and migraines (Siniatchkin et al 2003), among other conditions.…”
mentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42][43] The first evidence for altered interictal habituation in patients with migraine came from studies of contingent negative variation (CNV), a slow event related corti cal response representing higher mental functions. [44][45][46][47] Subsequently, deficient habituation was demonstrated for another event related potential, P300, which is eli cited in the process of decision making after visual 48 or auditory 49,50 stimulation. Deficient habitu ation was also subsequently described for several other modality specific evoked potentials: pattern reversal visual evoked potentials (VEPs), [33][34][35][36][37][38][39][40][41][42] visual evoked magneto encephalographic (MEG) responses, 43 auditory evoked potentials (AEPs), 51,52 and somatosensory evoked poten tials (SSEPs).…”
Section: Impaired Habituationmentioning
confidence: 99%